Conversion of waste‐soap and soap‐like materials into diesel and gasoline by catalytic pyrolysis using virgin soap as model. (26th November 2015) - Hussain, Zahid; Sulaiman, Shaharin Anwar; Gul, Humaira; Farooq, Sana; Khan, Khalid Mohammad; Gulab, Hussain; Naz, Muhammad Yasin
Abstract: In this work, soap was converted into a hydrocarbon‐rich product through catalytic pyrolysis using cement as a catalyst. The intention was to develop a new economical and effective method for preparing diesel and gasoline from soap waste in food processing. The optimum conditions for pyrolysis were investigated in a batch process under static conditions at different reactor temperatures, catalyst amounts, and reaction durations. The resulting oil product was analyzed using GC‐FID, GC‐MS, and FTIR. The best yield occurred at a reaction temperature of 400 °C for 60 min with 0.3 g/g (30 mass%) catalyst in soap waste, which resulted in 0.71 g/g (71 mass%) hydrocarbons with small fractions of pyran, ketone, and oxygenated compounds of mixed functional groups. The resulting liquid pyrolysate mainly consisted of diesel‐like oil with a small fraction of gasoline and some oils that had boiling‐point temperature ranges similar to kerosene.